Fighting tuberculosis in the EU/EEA: towards the new European Union standards on tuberculosis care. Issue 5 (November 2016) - Sotgiu, Giovanni; Beer, Netta; Aliberti, Stefano; Migliori, Giovanni Battista; van der Werf, Marieke J.
Tuberculosis (TB) is one of the most important clinical and public health infectious disease threats globally [1]. Its burden is substantial, with annually ∼9.6 million incident cases and 1.5 million deaths worldwide [1]. Since 1990, the previous decreasing global annual incidence trend has reversed due to the emergence of HIV/AIDS and the increase in TB–HIV co-infection. In addition, multidrug-resistant TB (MDR-TB) has emerged as a problem [1]. This change in the epidemiology has significantly challenged the control of TB through the World Health Organization (WHO) DOTS (directly observed treatment, short course) strategy, and forced international and national public health authorities to design and plan new operational strategies. New European Union standards for TB care and prevention to achieve WHO target of TB elimination by 2050 in EU/EEA http://ow.ly/NlhE302UXLV